Comparative Analysis of the Effectiveness of Regulation of Aeration Depending on the Quantitative Characteristics of Treated Sewage Water - Myroslav Malovanyy; Vira Shandrovych; Andriy Malovanyy; Igor Polyuzhyn (Journal of Chemistry)
Monitoring of work of the aeration tanks of operating town treatment plants is done. Based on the obtained results a conclusion has been drawn that sewage water is improperly treated from ammonium nitrogen. The velocity of the aeration process, depending on the concentration of dissolved oxygen and ammonium nitrogen, is investigated. The obtained investigation data became the basis for modeling the aeration process in industrial conditions depending on the required initial concentration of ammonium nitrogen.